Circulating Tumor Cells Enumerated by a Centrifugal Microfluidic Device as a Predictive Marker for Monitoring Ovarian Cancer Treatment: A Pilot Study - Hyera Kim; Minji Lim; Jin Young Kim; So-Jin Shin; Yoon-Kyoung Cho; Chi Heum Cho (Diagnostics, 2020)
We investigated the size-based isolation and enumeration of circulating tumor cells (CTCs) using a centrifugal microfluidic device equipped with a fluid-assisted separation technology (FAST) disc. We further assessed the correlations among CTCs, cancer antigen-125 (CA125) levels, and clinical course of the disease in a prospective analysis of 47 serial blood samples collected at multiple time-points from 13 ovarian cancer patients. CTCs were isolated from whole blood using the FAST disc and were classified as epithelial cell adhesion molecule (EpCAM)/cytokeratin+, CD45−, and 4′,6-diamidino-2-phenylindole (DAPI)+. Mean CTC count at baseline was 20.2; 84.62% of patients had more than one CTC at baseline and had decreased CTCs counts after surgery and chemotherapy. The CTC counts in eight patients with complete responses were <3. CTC counts were correlated with CA125 levels in three patients without recurrence; they were elevated in three patients with recurrence and normal CA125 concentrations. CTC counts and CA125 levels showed high concordance with directional changes (increasing 71.4%; non-increasing 75.0%). CTC counts showed higher associations with clinical status, sensitivity (100.0% vs. 60.0%), positive predictive value (55.6% vs. 42.9%), and negative predictive value (100.0% vs. 87.5%) than CA125 levels. CTC counts were better associated with treatment response and recurrence than CA125 levels.